The Utility of Physiological Measures in Assessing the Empathic Skills of Incarcerated Violent Offenders. (January 2022) - Palix, Julie; Abu-Akel, Ahmad; Moulin, Valérie; Abbiati, Milena; Gasser, Jacques; Hasler, Christopher; Marcot, Dominique; Mohr, Christine; Dan-Glauser, Elise
Since lack of empathy is an important indicator of violent behaviors, researchers need consistent and valid measures. This study evaluated the practical significance of a potential physiological correlate of empathy compared to a traditional self-report questionnaire in 18 male violent offenders and 21 general population controls. Empathy skills were assessed with the Interpersonal Reactivity Index (IRI) questionnaire. Heart-Rate Variability (HRV) was assessed with an electrocardiogram. The RMSSD (Root Mean Square of the Successive beat-to-beat Differences), an HRV index implicated in social cognition, was calculated. There were no group differences in IRI scores. However, RMSSD was lower in the offender group. Positive correlations between RMSSD and IRI subscales were found for controls only. We conclude that psychometric measures of empathy do not discriminate incarcerated violent offenders, and that the incorporation of psychophysiological measures, such as HRV, could be an avenue for forensic research on empathy to establish translatable evidence-based information.